Implementasi Metode Langsung dalam Program “Arabic Camp” di Madrasah Ibtidaiyah - Yasin, Agus; Tazali, Rahmad Maulana; Gandhi, Zain Irsyad (Study Program of Arabic Language Teaching, 2023)
This research aims to determine the application of the direct method in the Arabic Camp program at MI PAS Baitul Qur'an Gontor. This research uses descriptive qualitative research, and case study data to implement direct methods in the